2007
DOI: 10.29313/mediator.v8i1.1243
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation Theory

Abstract: The idea of Cultivation Theory was first addressed by George Gerbner with his colleagues of Annenberg School of Communication, Pennsylvania (1969). Based on previous research about cultural indicators conducted by the same researcher, cultivation analysis focused on mass media impact on everyday life. Another important findings from cultivation analysis was the categorization of television audience to two different classes: heavy viewers and light viewers. Among those two, heavy viewer became the main concern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The representation of women in the media, which is continuously accepted by the audience, can eventually be considered as a true representation of the reality of women. This assumption is in line with one of Gerbner's cultivation theory hypotheses which states that "the more time a person spends watching television, the stronger the tendency is for that person to equate television reality with social reality" [3][4][5][6].…”
Section: Introductionmentioning
confidence: 55%
“…The representation of women in the media, which is continuously accepted by the audience, can eventually be considered as a true representation of the reality of women. This assumption is in line with one of Gerbner's cultivation theory hypotheses which states that "the more time a person spends watching television, the stronger the tendency is for that person to equate television reality with social reality" [3][4][5][6].…”
Section: Introductionmentioning
confidence: 55%
“…As for the latest findings, the results of interview and documentary study showed that marine leadership character education was conducted with a systematic design using terminology of "cultivation." This term is different from the use of cultivation in the theory of communication from Gerbner and his friends conceptualized in the 1960s and 1970s as explained by Saefuddin & Venus (2007). It is also different from many kinds of research presenting the character cultivation in their titles such as from the research conducted by Wartin (2012); Arifin, Bafadal, Imron, & Sonhadji (2017).…”
Section: Discussionmentioning
confidence: 92%
“…Analisis kultivasi merupakan tahap lanjutan dalam paradigma penelitian awal Gerbner tentang efek media, yaitu indikator budaya, yang (1) mengkaji proses kelembagaan dalam produksi isi media, (2) citra isi media (impression), (3) hubungan antara terpaan pesan televisi dengan keyakinan dan perilaku khalayak. Teori kultivasi adalah proses kumulatif dimana tayangan media massa mampu menumbuhkan persepsi atau keyakinan terhadap realitas sosial khalayaknya (Saefudin & Venus, 2005).…”
Section: Hasil Dan Pembahasan Kajian Teori: Komunikasi Massa Teori Ku...unclassified